miRNA-dependent translational repression in the Drosophila ovary. - Reich, J.; Snee, M.J.; Macdonald, P.M. (PLoS ONE, 2009)
The Drosophila ovary is a tissue rich in post-transcriptional regulation of gene expression. Many of the regulatory factors are proteins identified via genetic screens. The more recent discovery of microRNAs, which in other animals and tissues appear to regulate translation of a large fraction of all mRNAs, raised the possibility that they too might act during oogenesis. However, there has been no direct demonstration of microRNA-dependent translational repression in the ovary.Here, quantitative analyses of transcript and protein levels of transgenes with or without synthetic miR-312 binding sites show that the binding sites do confer translational repression. This effect is dependent on the ability of the cells to produce microRNAs. By comparison with microRNA-dependent translational repression in other cell types, the regulated mRNAs and the protein factors that mediate repression were expected to be enriched in sponge bodies, subcellular structures with extensive similarities to the P bodies found in other cells. However, no such enrichment was observed.Our results reveal the variety of post-transcriptional regulatory mechanisms that operate in the Drosophila ovary, and have implications for the mechanisms of miRNA-dependent translational control used in the ovary.